A dynamic physicochemical model for chemical phosphorus removal. (15th April 2015) - Hauduc, H.; Takács, I.; Smith, S.; Szabo, A.; Murthy, S.; Daigger, G.T.; Spérandio, M.
Abstract: A dynamic physico-chemical model for chemical phosphorus removal in wastewater is presented as a tool to optimize chemical dosing simultaneously while ensuring compliant effluent phosphorus concentration. This new model predicts the kinetic and stoichiometric variable processes of precipitation of hydrous ferric oxides (HFO), phosphates adsorption and co-precipitation. It is combined with chemical equilibrium and physical precipitation reactions in order to model observed bulk dynamics in terms of pH. The model is calibrated and validated based on previous studies and experimental data from Smith et al. (2008) and Szabo et al. (2008) as a first step for full-plant implementation. The simulation results show that the structure of the model describes adequately the mechanisms of adsorption and co-precipitation of phosphate species onto HFO and that the model is robust under various experimental conditions. Graphical abstract: Highlights: A dynamic physico-chemical model for chemical P removal in wastewater is developped. The model describes the precipitation of hydrous ferric oxides (HFO) and its aging. It describes the adsorption and co-precipitation of phosphates onto/into HFO flocs. The model is robust under various chemical and physical experimental conditions.